The development of a computerized heuristic production scheduling algorithm based on the synchronous manufacturing (OPT) principles - Turner, V. K.(Vaughan Keith) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ing.) -- University of Stellenbosch, 1992.